KERAGAMAN SOSIAL DAN TOLERANSI ANTARBUDAYA DI INDONESIA - Irma Muti; Sudianto (Prosiding Seminar Nasional Indonesia, 2025)
Social diversity and intercultural tolerance in Indonesia, an archipelago with extraordinary cultural richness. With more than 17,000 islands, 1,340 ethnic groups, and 718 regional languages, Indonesia is a clear example of a multicultural society. The research method used is literature. The results show that while Indonesia's cultural diversity is a source of national wealth, it can also be a potential source of conflict if not managed properly. The research identified key strategies in building intercultural tolerance, including multicultural education, intercultural dialogue, inclusive public policies, use of media and technology, and active participation in cross-cultural activities. As such, intercultural tolerance is a vital element in maintaining the unity of the Indonesian nation, and an important foundation for sustainable national development.